Therapeutic potential of extracellular vesicles in inflammatory diseases - Xiaojian Huang; Shen Zhang; Zhenzhen Wang (Extracellular Vesicle, 2025)
Extracellular vesicles are spherical lipid bilayer vesicles composed of lipids, proteins and nucleic acids that could deliver signaling molecules into target cells to regulate their function and biological processes. Recently, increasing numbers of studies have demonstrated the therapeutic potential of extracellular vesicles (EVs) in inflammatory diseases by migrating the inflammatory responses and ameliorating physiological deteriorations, as well as promoting angiogenesis and mediating immune responses. In this review, we mainly focused on the biological and molecular functions of EVs in anti-inflammatory activity and their protective roles in many kinds of inflammation diseases, including pneumonia, neuroinflammatory diseases, inflammatory bowel disease, osteoarthritis, rheumatoid arthritis, cardiovascular disease, dry eye disease, periodontitis, diabetic wounds and systemic lupus erythematosus. Furthermore, we further summarized the underlying therapeutic mechanisms of EVs in inflammatory diseases and discussed the current challenges and future perspectives of EVs in clinical applications, providing an insight into the potential of EVs as therapeutic agent for other diseases.